Variations and characteristics of the various clinical phenotypes in a cohort of Nigerian sickle cell patients. Issue 1 (1st January 2021) - Duru, Augustine; Madu, Anazoeze Jude; Okoye, Helen; Nonyelu, Charles; Obodo, Onochie; Okereke, Kelechi; Madu, Kenechi
ABSTRACT: Background: Sickle cell anaemia affects about 4 million people across the globe, making it an inherited disorder of public health importance. Red cell lysis consequent upon haemoglobin crystallization and repeated sickling leads to anaemia and a baseline strain on haemopoiesis. Vaso-occlusion and haemolysis underlies majority of the chronic complications of sickle cell. We evaluated the clinical and laboratory features observed across the various clinical phenotypes in adult sickle cell disease patients. Methods: Steady state data collected prospectively in a cohort of adult sickle cell disease patients as out-patients between July 2010 and July 2020. The information included epidemiological, clinical and laboratory data. Results: About 270 patients were captured in this study (165 males and 105 females). Their ages ranged from 16 to 55 years, with a median age of 25 years. Sixty-eight had leg ulcers, 43 of the males had priapism (erectile dysfunction in 8), 42 had AVN, 31 had nephropathy, 23 had osteomyelitis, 15 had osteoarthritis, 12 had cholelithiasis, 10 had stroke or other neurological impairment, 5 had pulmonary hypertension, while 23 had other complications. Frequency of crisis ranged from 0 to >10/year median of 2. Of the 219 recorded, 148 of the patients had been transfused in the past, while 71 had not. Conclusion: The prevalence of SLU, AVN, priapism, nephropathy and the other complications of SCD show some variations from other studies. This variation in the clinical parameters across different clinical phenotypes indicates an interplay between age, genetic and environmental factors.